Assessing rule understanding and consistency among WUKF karate coaches, instructors, and referees in kata competitions - Dancescu, D.; Iorga, V. (Journal of Physical Education and Sport, 2024)
Problem statement Assessing kata performance in karate competitions, especially in the World Union of Karate-Do Federations (WUKF), is influenced by the subjective interpretation of criteria such as "strength," "speed," "rhythm," and "kime." This subjectivity can lead to scoring inconsistencies and disputes among referees, coaches, and athletes.